Studies on Synergistic Effects of Thermal Treatment on Physicochemical Properties of Starch Blends - Kumar, K. Jayaram (Asian Journal of Pharmaceutics (AJP), 2021)
Aim: The aim of the study was to evaluate the potential synergistic effect of natural and thermally modified starch blends from maize and potato. Materials and Methods: The maize and potato starches were combined in proportions of 1:1 (NSB1) and 1:2 (NSB2) and thermally treated (pregelatinization and retrogradation). For their application as excipients, these thermally treated starch blends were compared to natural starch blends for physicochemical parameters such as moisture content, water holding capacity, swelling and solubility, and amylose concentration. Results and Discussion: The amylose content of the heat-treated gums increased, indicating that it could be used in colon medication administration. The increase in water holding capacity from 218.13 ± 0.13% to 732.27 ± 0.34% demonstrates its promise in hydrogel creation. The moisture percentage of all the blends was in the range of 10.10 ± 0.03%–15.42 ± 0.03%, which were well within the range specified in Indian Pharmacopoeia. All of the samples’ pH levels were determined to be mildly basic (7.15–7.46). Conclusion: The potato and maize modified starch blends demonstrated a promising synergistic impact compared to native blends as an adjuvant in the formulation of various drug delivery systems.